(untitled) (Journal of Economic Additions, 2025)
This study aims to examine the impact of service recovery justice strategies on user satisfaction, based on a conceptual model tested through an online questionnaire. A suitable sample of 335 users who experienced service failures while using the BaridiMob application was obtained. Using Structural Equation Modeling (SEM) via SmartPLS v4, the results revealed that the three dimensions of service recovery justice have a statistically significant impact on the satisfaction of digital financial service users. These findings provide scientific insights to enhance the effectiveness of digital service recovery strategies and improve the overall user experience within the services offered by Algeria Post. Jel Classification Codes: O33, D12, L86